English Language Immersion: Local Wisdom-Based Reading Material for Naposo Nauli Bulung in EFL Context - Rica Umrina Lubis; Sartika Dewi Harahap; Aprianti Hasibuan (Universitas Dian Nuswantoro, 2023)
Abstract. Mastering English is very urgent considering Indonesia as a developing country has crucial status in the worldwide consciousness both political, social, cultural, and economic. Hence, the ability of international connections has been attached to the official program of what children learn at school from fundamental to undergraduate students. The study aimed to implement English Language Immersion: Local Wisdom-Based Reading Material as a platform to resolve a solution and to find Naposo Nauli Bulung perception of this program. The target of the study was 90 Naposo Nauli Bulung, ranging in age from 12-25 years old who have not gotten married. They learn English based on local reading material which provides cross-cultural understanding and communicate more effectively in English as a foreign language. The research was a qualitative and quantitative method. The instruments of the study were interview guidelines, questionnaires, and observations. The process of English Language Immersion in Local Wisdom-Based Reading Material through four stages namely (Orientation, Preparation, Implementation, and Evaluation). According to the questionnaire results, 95% of respondents said the program is interesting, 95% said the immersion includes a component of local wisdom, 97% said the reading materials are simple to understand, 95% said each topic has a list of difficult words, 95% said the reading materials encourage readers to think critically, 95% said each topic contains tasks or assignments, and 96% said the program enables them to learn more about the people and culture.Keywords: English Language Immersion; local wisdom; reading material; EFLAbstrak. Penguasaan bahasa Inggris sangat mendesak mengingat Indonesia sebagai negara berkembang memiliki status krusial dalam kesadaran dunia baik politik, sosial, budaya maupun ekonomi. Oleh karena itu, kemampuan koneksi internasional telah melekat pada program resmi dari apa yang dipelajari anak-anak di sekolah dari dasar hingga sarjana. Tujuan dari penelitian ini adalah untuk mengimplementasikan English Language Immersion: Local Wisdom-Based Reading Material sebagai platform untuk menyelesaikan sebuah solusi dan mendapatkan persepsi Naposo Nauli Bulung terhadap program ini. Sasaran penelitian adalah 90 Naposo Nauli Bulung, berusia 12-25 tahun yang belum menikah. Mereka belajar bahasa Inggris berdasarkan bahan bacaan lokal yang memberikan pemahaman lintas budaya dan berkomunikasi lebih efektif dalam bahasa Inggris sebagai bahasa asing. Penelitian ini menggunakan metode kualitatif dan kuantitatif. Instrumen penelitian berupa pedoman wawancara, angket, tes dan observasi. Proses English Language Immersion: Local Wisdom-Based Reading Material melalui empat tahapan yaitu (Orientasi, Persiapan, Pelaksanaan, dan Evaluasi). Dari hasil kuesioner yang diberikan, 95% menjawab program ini menarik, 95% menyatakan program ini mengandung unsur kearifan lokal, 97% mengatakan bahan bacaannya mudah dipahami, 95% menjawab setiap topik memiliki kosakata yang sulit, 95% menjawab bahan bacaan memungkinkan pembaca untuk berpikir secara mendalam, 95% mengatakan setiap topik berisi tugas atau latihan, dan 96% menyatakan bahwa program ini memungkinkan mereka untuk mendapatkan wawasan tentang budaya dan tradisi masyarakat setempat.Kata kunci: English Language Immersion; kearifan lokal; bahan bacaan; EFL